Application of nanomaterials in waterborne coatings: A review - Hongrui Yao; Lijuan Li; Wanshen Li; Duo Qi; Wanlu Fu; Na Wang (Resources Chemicals and Materials, 2022)
Combining nanomaterials and waterborne resins is an effective way to obtain high-performance waterborne coatings. This paper provides a comprehensive overview on waterborne nanocomposite coatings based on the latest research progress at home and abroad. Specifically, the characteristics of zero-dimensional (0D), one-dimensional (1D), two-dimensional (2D) and binary hybrid (0D/1D, 0D/2D, 1D/2D, 2D/2D) nanomaterials and their applications in waterborne coatings are coherently reviewed. Subsequently, various modification methods of nanomaterials, especially noncovalent modification and covalent modification, are analyzed in detail. Additionally, the enhancement mechanisms of nanomaterials enhancing the corrosion resistance of waterborne nanocomposite coatings are also discussed, including physical barrier mechanism and electrochemical mechanism. Finally, based on the above discussion, the outlooks for the future design of waterborne nanocomposite coating are presented.